Derivatization And Conjugation Of Folic Acid To Improve Its Affinity Towards Folate Receptor Alpha On Cancerous Membrane Bilayer: An In Silico Insight - Althiabat, Mohammad Gasem Mohammad (2024)
Effective targeting of cancerous cells with minimal side effects remains a significant challenge in the development of chemotherapeutic drugs. This study presents a novel in silico approach for targeting chemotherapeutic drug delivery to cancer cells using folic acid (FA) conjugated to β-cyclodextrin (βCD), aimed at enhancing selectivity via the interaction with folate receptor alpha (FRα). In a previous in silico study, enhanced targeting was demonstrated by tetrazole (FOL03) and benzothiophene (FOL08) folic acid derivatives, with FOL03 exhibiting superior affinity for FRα. In this study, molecular docking and molecular dynamics (MD) simulations was employed to assess the impact of βCD on the binding affinity and stability of FA, FOL03, and FOL08 conjugates with FRα. Additionally, replica exchange umbrella sampling (REUS) was used to examine the retention of conjugates and the chemotherapeutic agent 5-fluorouracil (FLU) within βCD's hydrophobic cavity under virtual simulated cancerous conditions which also include the lipid bilayer environment. In the non-inclusion systems, the docking scores show that FRα- FOL08-βCD exhibited stronger binding (-17.10 kcal/mol) than -FA-βCD (-15.20 kcal/mol) and -FOL03-βCD (-15.50 kcal/mol). All ligands bound in a similar pose within the active site of FRα. MD simulations over 100 ns demonstrated that the FRα- FOL03-βCD complex maintained dynamic stability, showing minimal conformational changes. Quantum mechanical analysis, using MOPAC-2016 and the PM7 method, corroborated the MD simulations, identifying the electronic properties that confer xviii stability to the FRα-FOL03-βCD complex.